CRISPR/Cas-enabled paper microfluidic device to detect SARS- CoV-2 and its variants for wastewater-based epidemiology - Hui, Qingxin (Cranfield University, 2025)
Wastewater-based epidemiology (WBE) has been demonstrated to be a powerful tool for monitoring public health through the detection of biomarkers, such as drugs and pathogens, in wastewater. During the COVID-19 pandemic, it evolved into a significant supplementary approach to clinical diagnostics, offering capabilities as an early warning system, enabling population-level infection monitoring, and tracking down the virus including the variants of concern. However, current methods for wastewater analysis are heavily dependent on the centralized laboratory which requires expensive equipment, specialized personnel, and result in slow turnround. This thesis addresses these critical challenges by developing innovative approaches for the detection of SARS-CoV-2 and its variants, combining molecular diagnostics with field- deployable paper microfluidic devices. A comparative analysis of polyethylene glycol (PEG) precipitation and ultrafiltration for concentrating SARS-CoV-2 RNA from wastewater led to the development of an optimized protocol suitable for routine analysis. This protocol was applied for long-term monitoring of viral loads (N-gene) in a local wastewater treatment plant, providing valuable insights into infection trends. Additionally, a CRISPR/Cas12a-based fluorescent assay was developed to detect SARS-CoV-2 and its variants with high specificity and sensitivity, able to detect as low as 5 copies µL¯¹ . To enable on-site diagnostics, a portable paper microfluidic device was designed, integrating the optimized concentration methods and CRISPR/Cas12a assays. The device demonstrated a rapid detection of wastewater within 90 minutes for SARS-CoV-2 even without laboratory settings. This research findings advances WBE by bridging the gap between laboratory-based techniques and in-field testing. The technology provides a scalable, cost-effective platform for rapid and onsite monitoring SARS-CoV-2 and other pathogens, contributing significantly to global health management, particularly in resource-limited settings.
Cullen, David C. - Associate Supervisor
Keywords: Wastewater-based epidemiology; SARS-CoV-2 and Variants; CRISPR/Cas; Paper microfluidic device; Isothermal amplification